Quantitative evaluation and case studies of cleaner mining with multiple indexes considering uncertainty factors for phosphorus mines. (10th May 2018) - Dong, Longjun; Shu, Weiwei; Li, Xibing; Zhang, Junmin
Abstract: Since phosphorus is indispensable for the agricultural production, the demand for the phosphate rock is increasing with the agricultural development. For the sustainable development of phosphorus resources, the environmental pollution problem caused by the mining of phosphate rock should be solved efficiently. The cleaner production of phosphorus mines is exactly the basis and method for the sustainable development. Focusing on the environmental characteristics and main mining processes of phosphorus mines, 31 evaluation indexes were selected from 6 aspects including the management level, environmental protection level, mining technique, mining economic indicators, comprehensive utilization level of waste, and processed environmental level, to establish the comprehensive evaluation system for the cleaner production of phosphorus mines. The 5 qualitative evaluation indexes were quantified according to the classification criteria. The 26 quantitative evaluation indexes were determined through the measurement values. The single index measurement values were solved through the semi-trapezoid (ST) and semi-ridge (SR) membership functions. The weights of evaluation indexes were determined based on the theories of uncertainty measurement evaluation (UME) and analytic hierarchy process (AHP). The evaluation vectors were evaluated by applying the credible degree recognition criterion (CDRC) and the maximum membership principle (TMMP). A total of 8 coupled methods including ST-UME-CDRC, ST-UME-TMMP, ST-AHP-CDRC, ST-AHP-TMMP, SR-UME-CDRC, SR-UME-TMMP, SR-AHP-CDRC, and SR-AHP-TMMP were developed based on the combination of ST and SR membership functions, UME and AHP theories, as well as recognition criteria CDRC and TMMP. The cleaner production grades of two phosphorous mines in China were evaluated using these developed coupling methods. The future suggestions and approaches were given to improve cleaner production grades. Results show that ST-UME-CDRC method is the most reasonable among 8 coupled methods, which can not only evaluate the cleaner production grades of phosphorous mines, but also can provide a useful guidance to the sustainable development of phosphorous mines. Graphical abstract: Image 1 Highlights: Coupled methods for evaluating cleaner production of phosphorus mine are developed. Results proved the ST-UME-CDRC can evaluate cleaner production grades reasonably. The work is beneficial for improving the environmental and sustainable mining.